2018
DOI: 10.1038/s41467-018-04862-w
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of electrochemically triggered thermal and mechanical effects to aggravate failure in a layered cathode

Abstract: Electrochemically driven functioning of a battery inevitably induces thermal and mechanical effects, which in turn couple with the electrochemical effect and collectively govern the performance of the battery. However, such a coupling effect, whether favorable or detrimental, has never been explicitly elucidated. Here we use in situ transmission electron microscopy to demonstrate such a coupling effect. We discover that thermally perturbating delithiated LiNi0.6Mn0.2Co0.2O2 will trigger explosive nucleation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
176
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(189 citation statements)
references
References 30 publications
8
176
0
Order By: Relevance
“…Ultimately, they will evolve into larger cracks. [186] The presence of Li-site TM cations (rock-salt formation) and a high degree of stacking faults, presumably due to distortion of the oxygen framework (with high vacancy concentration), was also observed by Zhang et al [188] In any case, a (negative) cooperative effect of oxygen vacancies, structural dislocations, cracking, and rock-salt formation is likely to occur. TEM studies [186,187] revealed that intragranular cracking follows a strict crystallographic preference along the (003) plane.…”
Section: Mechanical Degradation Of Ni-rich Ncmmentioning
confidence: 64%
See 1 more Smart Citation
“…Ultimately, they will evolve into larger cracks. [186] The presence of Li-site TM cations (rock-salt formation) and a high degree of stacking faults, presumably due to distortion of the oxygen framework (with high vacancy concentration), was also observed by Zhang et al [188] In any case, a (negative) cooperative effect of oxygen vacancies, structural dislocations, cracking, and rock-salt formation is likely to occur. TEM studies [186,187] revealed that intragranular cracking follows a strict crystallographic preference along the (003) plane.…”
Section: Mechanical Degradation Of Ni-rich Ncmmentioning
confidence: 64%
“…[186,187] For example, in the case of NCM622, Yan et al [186] observed the presence of intragranular cracks in samples cycled to ≥4.65 V vs Li + /Li. TEM studies [186,187] revealed that intragranular cracking follows a strict crystallographic preference along the (003) plane. Hence, their formation as well as the underlying mechanism(s) must be understood in detail to achieve stable performance and longevity of Ni-rich NCM-based LIBs.…”
Section: Mechanical Degradation Of Ni-rich Ncmmentioning
confidence: 99%
“…[78] Consequently, the pulverized active material is gradually isolated from the electronically conductive matrix, resulting in severe capacity fade. On the structural perspective, the ultrahigh-Ni layered oxide suffers from dual-phase reaction mechanisms together with huge lattice distortion from the emerging H3 phase, which leads to disordered layered structure and particle pulverization after extensive cycling.…”
Section: Resultsmentioning
confidence: 99%
“…[12,16,17] One of the primary efforts on layered cathodes is further unlocking its capacity potential by narrowing the gap between the practical capacity and theoretical capacity. [26][27][28] The detrimental effects of cracking include fracture caused disintegration, [28] which leads to poor electronic conduction [29,30] and loss of active materials, and new surfaces exposure to electrolyte which results in cathode surface degradation [31][32][33] and electrolyte consumption. [18][19][20] The surface/interface degradations are attributed to the chemical reactions between cathode and electrolyte, which leads to cathode surface phase transition, [21,22] active material dissolution, [23] passivation layer formation, [24] electrolyte consumption, [25] and so on.…”
mentioning
confidence: 99%
“…However, increasing the utilization of alkaline ions, usually by elevating the high-charge cutoff voltage, results in structural instability of the layered cathodes, due to aggravated surface/ interface chemical degradations and bulk degradations. [27] Doping electrochemically inactive elements has been verified as an effective method to improve the electrochemical performance of layered cathodes. For bulk degradations, irreversible bulk phase transition and cracking are the two main failure mechanisms.…”
mentioning
confidence: 99%